Malnutrition is associated with diminished baseline and mycobacterial antigen – stimulated chemokine responses in latent tuberculosis infection. Issue 5 (November 2018) - Anuradha, Rajamanickam; Munisankar, Saravanan; Bhootra, Yukthi; Kumar, Nathella Pavan; Dolla, Chandrakumar; Babu, Subash
Highlights: Latent tuberculosis individuals with low body mass index exhibit diminished spontaneous production of several chemokines. These individuals also exhibit diminished production of several chemokines in response to TB antigen stimulation. Thus, low body mass index in latent TB contributes to diminished capacity to produce protective chemokines. Summary: Objectives: Previous studies have demonstrated a diminution in the baseline and mycobacterial antigen – specific cytokines in low body mass index (LBMI) individuals with latent tuberculosis infection (LTBI). We hypothesized that LBMI might be also associated with alteration in the baseline and antigen – stimulated levels of chemokines in LTBI. Methods: To test this hypothesis, we examined baseline, TB-antigen and mitogen stimulated levels of chemokines in these individuals and compared them with those with LTBI and normal BMI (NBMI). Results: LBMI with LTBI is characterized by diminished baseline levels of CCL1, CCL4, CCL11, CXCL1, CXCL9, CXCL10 and CXCL11 in comparison to NBMI with LTBI. Similarly, LTBI with LBMI is also characterized by diminished TB-antigen stimulated levels of CCL1, CCL2, CCL3, CCL4, CCL11, CXCL1, CXCL2, CXCL9, CXCL10 and CXCL11. In contrast, there were no significant differences in the mitogen stimulated chemokine levels between the groups. Finally, there was a significant positive correlation between BMI and CCL1, CCL4, CCL11, CXCL11, CXCL2, CXCL9 and CXCL11 levels in LTBI individuals. Conclusions: Therefore, our data reveal that LTBI subjects with low BMI are characterized by diminished levels of a variety of important chemokines, providing a novel biological mechanism for the increased risk of developing active TB.